Assessment of Metabolic Syndrome and Kidney and Heart Function in Childhood Cancer Survivors - Aleksandra Janecka; Joanna Stefanowicz; Anna Owczarzak; Marek Tomaszewski; Tomasz Batko; Ninela Irga-Jaworska (MDPI AG, 2023)
Background: The survivors of childhood cancer suffer from a number of long-term side effects. These include atherosclerosis and cardiovascular diseases (CVDs) that develop earlier in adulthood than in the rest of the population. The aim of this study was to identify prognostic factors of developing atherosclerosis before the development of symptomatic CVD. Methods: A total of 141 children that were 7-18 years old were examined; there were 116 survivors of childhood malignancies (hematopoietic and lymphoproliferative malignancies-52; neuroblastoma-22; Wilms tumor-24; other solid tumors-18) and 25 healthy controls. Anthropometric measurements, blood pressure measurements, ultrasonography of the abdomen, echocardiography, and laboratory tests were performed. Results: There were no significant differences in gender distribution, time from the end of the treatment, weight, BMI, prevalence of central obesity, blood pressure and resistive index of the renal arteries, lipid profile, or glucose and fibrinogen levels. Patients with solid tumors had a significantly lower height and worse renal function. Patients with hematological malignancies significantly presented the lowest shortening fraction of the left ventricle. The salusin β levels were significantly higher in the control group than among the patients. Conclusions: The type and severity of side effects are closely related to the type of neoplasm and the treatment that has been undergone. Careful observation and regular follow-up are necessary.